The Impact of Debt Strucutre, Operational Capability, Liquidity, Profitability, and Capital Structure Toward Financial Risk (Case Research : PT. Gapura Angkasa) - Indra Wibiksana, Bayu; Maya Damayanti, Sylviana (Journal of Economics and Business UBS, 2023)
In order to finance its operations and investment activities, one of PT. Gapura Angkasa's funding sources is debt, a kind of external funding for the company. Debt policy in a company is very important to be evaluated and analyzed properly because many companies will experience success with accuracy in making debt decisions. Debt policy can have an impact on optimizing the use of funds in the company. A company's financial troubles and likelihood of filing for bankruptcy may be impacted by its level of debt. The objective of research is for investigate the impact of debt structure, operational capability, liquidity, profitability, and capital structure on financial risk. This research utilizes secondary data sources in the form of financial reports from companies. The data utilized is PT. Gapura Angkasa's financial report data from 2017 to 2021. In this research, the independent factors include debt structure, operational capability, liquidity, profitability, and capital structure, whereas the dependent variable is financial risk. This research employs multiple regression with the aid of the SPSS application for its data analysis. Accordingly to the findings of the research, debt structure got a negative impact on financial risk. Similarly, operational competency negatively impacts financial risk. However, neither liquidity nor profitability nor capital structure had any impact on financial risk. The debt structure should be a concern for PT. Gapura Angkasa's management in order to retain the usage of debt while ensuring that the company's debt is not excessive and that its working capital continues to grow.